Anaesthetic Safety: What Do Patients Understand and Expect? - Edwards, Lowri (Trinity Student Medical Journal, 2022)
• Patients’ satisfaction depends on their prior expectations. These, in turn, are influenced by their understanding of a procedure. • Provision of adequate pre-operative information can improve patients’ perioperative outcomes. • Patients’ understanding of information provided may be optimised by employment of techniques including consolidation by multiple team members throughout the pre-operative period and the presence of a companion during consultations. • A relative lack of awareness surrounding the anaesthesia and the role of the anaesthesiologists are contributing factors towards patient anxiety. • A careful balance must be obtained between providing enough information to facilitate informed decision-making without causing unnecessary stress. • Causes of patients’ perioperative anxiety are variable and are often underestimated. Efforts to acknowledge and alleviate this anxiety are known to have therapeutic benefit. • Patients’ expectations of anaesthesia are influenced by a multitude of individual, social and cultural factors. This highlights the importance of meaningful discussion with the patient and a tailored approach to the pre-operative consenting procedure. • In light of the COVID-19 pandemic, the good health of healthcare workers is increasingly being recognised as a priority for ensuring patient safety.